The determinants of university participation in Canada (1977 - 2003) - Louis N. Christofides; Michael Hoy; Ling Yang (Institute for the Study of Labor (IZA), 2008)
The decision to attend university is influenced by the balance of the expected returns and costs of attending university, by liquidity constraints and capital market imperfections that may modify these calculations and, hence, by the family income of prospective students. Family circumstances also play a role. We examine the secular increase in the propensity of children from Canadian families, evident in annual surveys spanning two and a half decades, to attend university. We quantify the importance of these factors taking account of the greater propensity by young women than men to attend university and controlling for secular trends in socioeconomic norms that impinge on these decisions.
urn:nbn:de:101:1-20081126803
Keywords: I21; 330; University participation; parental education; university premium; gender; tuition; income; societal trends; Studium; Bildungsverhalten; Bildungsertrag; Familiensoziologie; Kanada